2020
DOI: 10.3126/jist.v25i2.33747
|View full text |Cite
|
Sign up to set email alerts
|

Study on Biological Activity of Litsea monopetala From Panchthar District of Nepal

Abstract: The Panchthar, a hilly district of Eastern Nepal, has several medicinal plants which are used by indegenous people for the treatments of different diseases. In the present work, phytochemical and biological activities of hexane, ethyl acetate, acetone, and methanol extracts of Litsea monopetala leaves from the Pachthar district were analyzed. The phytochemical screening demonstrated the presence of major secondary metabolites like flavonoids, alkaloids, terpenoids, polyphenols, glycosides, and proteins. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Previous studies have also shown the good antioxidant activity and high phenolic content of L. monopetala . 46 Further evaluation of the molecular mechanism of anti-inflammatory activity is necessary to determine the mechanism of NO inhibition. However, the genus Litsea has been reported to possess a wide range of secondary metabolites, including alkaloids, sesquiterpenes, flavonoids, lactones, lignans, and essential oil.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown the good antioxidant activity and high phenolic content of L. monopetala . 46 Further evaluation of the molecular mechanism of anti-inflammatory activity is necessary to determine the mechanism of NO inhibition. However, the genus Litsea has been reported to possess a wide range of secondary metabolites, including alkaloids, sesquiterpenes, flavonoids, lactones, lignans, and essential oil.…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemical screening of Ipomoea species also revealed the presence of tannins, saponins, flavonoids, triterpenes, phenols and alkaloids. Antimicrobial sensitivity results showed that methanolic extract had promising antibacterial and fungal activity at the highest concentration of 500 mg/ml [24].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an arabinoxylan has been documented in the mucilage of L. monopetala leaves, contributing to the comprehensive understanding of its phytochemical composition. 4,5 In our study, we focused our research on L. monopetala and we, here in, report the presence of two polyprenols, from an ethyl acetate extract of the leaf of the plant.…”
Section: Introductionmentioning
confidence: 99%